(untitled) (Transport systems and technologies, 2023)
An overview of modern trends in updating shunting locomotives, which are based on the installation of on-board energy storage devices, multi-diesel propulsion power plants, and power plants operated on hydrogen energy sources, was carried out. The necessity to take into account the operating conditions of a shunting diesel locomotive when choosing an upgrade option is shown. The operation modes of shunting diesel locomotives during shunting operations at the Козятин-I freight station during three shifts were considered. By analyzing the data of the БІС-Р onboard system and processing the route sheets, the parameters of the operating modes were determined. Calculations of diesel engine power utilization indicators were performed, according to which it was determined that the full use of the installed diesel generator power is 7.5...8.4%, and the maximum diesel power recorded under the studied operating conditions is about 50%. The duration of work with traction loads is 49.5...68.8% of the shift time. The longest - 55...60% of the total duration of work under traction - are modes with a power of 0...50 kW. The duration of work without load is 18.1...36.9% of the duration of the shift. The shunting work performed is related to the formation and disassembly of trains, including the use of a sorting slide, as a result of which the traction power transmission operates with a low efficiency. In order to reduce the consumption of fuel and energy resources when performing shunting work, it is necessary to update the fleet of locomotives for shunting work, the characteristics of which are adapted to the operating modes.